1979
DOI: 10.1007/bf00973997
|View full text |Cite
|
Sign up to set email alerts
|

The non-ossified pubis

Abstract: A group of syndromes is presented whose common characteristic is the absence of pubic ossification at birth with very slow posterior mineralization. This is a radiological finding of interest as it has not been described in other entities. In all the cases shown, moreover, a variable degree of delay in bone age is observed. The increase of space between the pubic bones described in these syndromes is fictious, as it really signifies the existence of non-ossified cartilage. Therefore, they must be differentiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This feature is also seen in achondrogenesis, hypochondrogenesis (short long bones), Sjogren Larssen syndrome, Wolf syndrome, and spondyloepiphyseal dysplasia congenital. [ 15 ]…”
Section: Ossificationmentioning
confidence: 99%
“…This feature is also seen in achondrogenesis, hypochondrogenesis (short long bones), Sjogren Larssen syndrome, Wolf syndrome, and spondyloepiphyseal dysplasia congenital. [ 15 ]…”
Section: Ossificationmentioning
confidence: 99%
“…Among the three constituents of the hip bone, the pubis is the last to ossify, between months 5 and 6 of gestation. The primary ossification center is located within the superior pubic ramus, in front of the acetabulum and just in the close vicinity of the obturator and femoral nerves [ 4 , 9 , 10 , 16 , 24 , 26 ]. During the early development, the pubic ossification center is dumbbell-shaped [ 24 ] or bean-shaped [ 4 ], and constitutes the smallest and most dainty component in the whole pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…At birth, the pubis is somewhat oval, with its articular surface pointed anteriorly [ 24 ] and with its superior pubic ramus considerably ossified [ 9 ]. Basing on 1286 radiographs of full-term neonates, Caffey and Madell [ 4 ] found that the superior pubic ramus was ossified in all examined cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct evaluation and correlation can orient and define the diagnosis of certain processes at an early stage. 21 No treatment is necessary.…”
Section: Delayed Ossification Of the Pubic Ramimentioning
confidence: 99%